2020
DOI: 10.3390/polym13010120
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Imprinted Polymers for the Removal of Antide-Pressants from Contaminated Wastewater

Abstract: Selective serotonin reuptake inhibitors (SSRIs) are a class of antidepressants regularly detected in the environment. This indicates that the existing wastewater treatment techniques are not successfully removing them beforehand. This study investigated the potential of molecularly imprinted polymers (MIPs) to serve as sorbents for removal of SSRIs in water treatment. Sertraline was chosen as the template for imprinting. We optimized the composition of MIPs in order to obtain materials with highest capacity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 60 publications
0
13
0
2
Order By: Relevance
“…High performance liquid chromatograph coupled with a diode array detector (HPLC-DAD) was used for the different detections. Despite the small surface area of the synthesized polymers that ranged between 27.4 and 193.8 m 2 g −1 , as compared to that of the activated carbon at 1400 m 2 g −1 , their sorption capabilities in wastewaters were generally superior [185].…”
Section: Pharmaceutical Productsmentioning
confidence: 98%
“…High performance liquid chromatograph coupled with a diode array detector (HPLC-DAD) was used for the different detections. Despite the small surface area of the synthesized polymers that ranged between 27.4 and 193.8 m 2 g −1 , as compared to that of the activated carbon at 1400 m 2 g −1 , their sorption capabilities in wastewaters were generally superior [185].…”
Section: Pharmaceutical Productsmentioning
confidence: 98%
“…In aquatic organisms, they cause changes in growth processes, and feeding and survivorship behavior (Sehonova et al 2019 ; Stoczynski and van den Hurk 2020 ). Recently, a molecularly imprinted polymer based on methacrylic acid as functional monomers and sertraline as a template has been used for removal of not only targeted template but for the whole class of selective serotonin reuptake inhibitors has been reported by Gornik et al ( 2021 ); maximum imprinting factor was found to be 3.7, and the maximum capacity for sertraline was estimated at 72.6 mg g −1 . The molecularly imprinted polymers can form more non-specific interactions with the targets due to their high surface area and pore volume, thus improving the overall removal efficiency in wastewater treatment.…”
Section: Molecularly Imprinted Polymersmentioning
confidence: 99%
“…Selanjutnya MIP dicuci dengan aquabidest, metanol, asetonitril. Pencucian menggunakan air untuk menghilangkan residu asam asetat karena residu asam ini dapat mempengaruhi pada proses rebinding selanjutnya [37] [38]. Metanol digunakan untuk menarik CAP lebih banyak pada MIP.…”
Section: Gambar 3 Representasi Skematis Dari Proses Pencetakan Moleku...unclassified